2015
DOI: 10.1080/17461391.2015.1086818
|View full text |Cite
|
Sign up to set email alerts
|

Ankle and knee kinetics between strike patterns at common training speeds in competitive male runners

Abstract: The purpose of this study was to investigate the interaction of foot strike and common speeds on sagittal plane ankle and knee joint kinetics in competitive rear foot strike (RFS) runners when running with a RFS pattern and an imposed forefoot strike (FFS) pattern. Sixteen competitive habitual male RFS runners ran at two different speeds (i.e. 8 and 6 min mile(-1)) using their habitual RFS and an imposed FFS pattern. A repeated measures analysis of variance was used to assess a potential interaction between st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 42 publications
4
51
2
1
Order By: Relevance
“…In the EG, the peak knee extension moment was significantly reduced by 13.8% after the 12-week gait retraining. Lower peak knee extension moment was also found among FFS compared with RFS in other studies [19,29,33]. The abovementioned changes in the EG in the present study were not observed in the CG.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…In the EG, the peak knee extension moment was significantly reduced by 13.8% after the 12-week gait retraining. Lower peak knee extension moment was also found among FFS compared with RFS in other studies [19,29,33]. The abovementioned changes in the EG in the present study were not observed in the CG.…”
supporting
confidence: 73%
“…Liao et al focused on the difference in patellofemoral joint stress between participants with or without patellofemoral joint pain based on the finite element model and found that the peak PFS of runners with 7 BioMed Research International pain was larger than that of runners without pain and knee moment was regarded as a predictive factor [34]. Previous research suggests that FFS had lower vGRF than RFS [35], FFS could have a larger ROM of ankle [33], and the mechanical properties of the Achilles tendon can be strengthened by forefoot strike. The improvement in the loading ability of the Achilles tendon is beneficial to the calf to play a greater role in the impact phase.…”
mentioning
confidence: 99%
“…Most previous studies focused on the direct relationship between fatigue and injury, especially the biomechanical changes in the lower extremities before and after fatigue [15][16][17][18][19]. For instance, Radzak et al [14] reported the biomechanical asymmetry (e.g., loading rate and knee/vertical stiffness) of the lower limbs before and after fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings basically confirm the data of the literature, with FFS leading to higher MPF and RFS leading to higher LR. 11 The higher vertical LR in RFS may be ascribed to the first impact peak occurring immediately in the early part of the stance phase by landing directly with the heel. 1,11,15 The higher vertical MPF in FFS may be a consequence of the reduced ground contact time when performing FFS.…”
Section: Discussionmentioning
confidence: 98%
“…So far, most studies have compared the biomechanics pattern of RFS and FFS by only measuring the vertical forces based on the GRF without differentiating between the different joints. 11,15,28 Others have implemented the differentiation between different joints of the lower limb focusing primarily on axial contact forces in forefoot and rearfoot runners. 24 Generally, shear forces are much smaller than the vertical forces that arise during running and therefore may not contribute to an injury potential.…”
Section: Discussionmentioning
confidence: 99%